Ethmoidal dural Arteriovenous Fistula- A case report (Journal of Brain and Spine Foundation Nepal, 2020)
Ethmoidal dural arteriovenous fistulas (dAVF) are a rare type of dAVF present in the anterior cranial fossa. There are usually fed by the ethmoidal artery and drains into superior sagittal sinus. Due to its high flow nature, they are considered a challenging case for surgery and usually present with frontal lobe hematoma or seizure. Here, is a similar case report of a 52-year-old gentleman who presented with sequel of frontal lobe hematoma and was managed surgically with clipping of feeder and excision of fistula.